Evaluation study on grid-connected PV system at University of Malaya - Kamali, S.K.; Mekhilef, Saad (2009)
This paper presents the complete design of a photovoltaic installation that may be either used for internal electric consumption or for sale using the renewable energy incentive program by the state of Malaysia (SURIA 1000 and so on.). Moreover in this article an economic and environmental study is carried out on PV solar energy installations connected to the Malaysian electrical grid system. The study has been performed on construction situated in the city of Kuala Lumpur (with an average irradiation value approximately equal to 5.4 kWh/m2/d) based on an analysis of the technical and financial viability of a grid connected PV systems. Initially, the study is performed; proposing different scenarios where different values of interest rates and initial costs incentives applied. The following parameters are used to determine the profitability of a PV structure: the Net Present Cost (NPC), Renewable Fraction (RF) and Lifetime. Furthermore, the environmental benefits of PV systems connected to the grid have been evaluated.